Strengthening capacity for accessing and disseminating information for policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
In spite of its oil wealth, poverty plagues Nigeria. The Federal Government of Nigeria has recognized that improved agricultural performance is critical to poverty reduction, since the majority of the nation’s poor depend on agriculture for their livelihood. With this renewed focus on agriculture, the sector’s growth rate has improved 6 to 7 percent annually since 2003. However, the sector remains hampered by weak economic and stakeholder linkages, poor information management, and an overall weak policy environment. The Rural Economy Knowledge Support System (REKSS) is, along with Policy Themes, one of the two program components of the Agricultural Policy Support Facility (APSF. REKSS is a centralized system for managing and streamlining knowledge on the rural economy and it identifies important knowledge and information gaps and facilitates location-specific analysis of rural development and food security policies and strategies. REKSS supports strategic planning and capacity building in agriculture and rural development by working with Nigerian partners to: Offer courses and seminars that strengthen policy analysis and design; Compile agriculturally relevant datasets and document archives, especially related to the poverty, gender, and environmental dimensions of the sector; Build the evidence base needed for agricultural and rural development, including analyses to inform public and private sector investments; and Disseminate information and reinforce communication networks to support strategic planning and policymaking in agricultural and rural development. To strengthen agricultural and rural development policymaking in Nigeria, the Federal Ministry of Agriculture and Water Resources (FMAWR), through APSF, is implementing several activities to support the research needed for evidence-based policymaking and to systematize the sharing of information. During the April 2008 APSF consultation workshop on “Sustaining Capacity for Supplying Evidence for Agricultural and Rural Development Policies” held at the University of Ibadan, participants discussed challenges faced by faculty and students in getting access to information resources for developing policy research, and identified a need to strengthen capacities for accessing and disseminating information required for policy research. This finding is premised on the need for a strong and guaranteed access to retrospective and current information to support advancement in agricultural policy and rural development research. Strengthening access to agriculture-relevant publications and supporting information dissemination provides the basis for high-quality agricultural research and supplying high-quality evidence to the government and other policymaking entities. To address some of the challenges identified at the April 2008 consultation workshop, APSF organized two workshops on strengthening capacity for accessing and disseminating information. The first workshop was held on November 13, 2008 at the International Institute for Tropical Agriculture (IITA), Ibadan and the second on November 18, 2008 at the International Center for Soil Fertility and Agricultural Development (IFDC), Abuja. This report provides a brief overview of the presentations delivered during the workshop, key comments/suggestions as well as workshop evaluation by the participants.